1965
DOI: 10.1136/gut.6.5.458
|View full text |Cite
|
Sign up to set email alerts
|

The stomach in tropical sprue.

Abstract: EDITORIAL SYNOPSIS The authors describe the results of a study of the gastric secretion and gastric histology of 15 control subjects and 30 patients with tropical sprue. Patients with sprue show a marked depression of gastric secretion and varying degrees of gastritis as compared with control subjects. There is no relation between the severity of the gastric lesion and the severity of the intestinal lesion. The possible aetiology of the gastritis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

1968
1968
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 16 publications
(12 reference statements)
3
7
0
Order By: Relevance
“…The results of the augmented histamine test showed a diminished acid output in patients with tropical sprue as has been observed by others (Floch et al, 1963;Vaish et al, 1965). In our patients, the significantly raised acid output observed with a suggested that low values for acid output on the augmented histamine test might at least partly be due to the lower doses of histamine administered, calculated in relation to their reduced body weights.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of the augmented histamine test showed a diminished acid output in patients with tropical sprue as has been observed by others (Floch et al, 1963;Vaish et al, 1965). In our patients, the significantly raised acid output observed with a suggested that low values for acid output on the augmented histamine test might at least partly be due to the lower doses of histamine administered, calculated in relation to their reduced body weights.…”
Section: Discussionsupporting
confidence: 89%
“…It is of inteiest to note that Vaish et al (1965) reported a marked increase in acid output in a patient with tropical sprue whose weight had increased by about 15 kg. between the two tests but the finding was unexplained.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gastric involvement consisting of atrophic or chronic gastritis, achlorhydria, or hypochlorhydria occurred in 75%, which is similar to levels in other series (Floch et al, 1963;Vaish et al, 1965;Baker and Mathan, 1971). The relatively low overall incidence of steatorrhoea (40%) is explained by the inadequate fat content of the diets early in the study.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, apart from these anaemic states, other patients may show recovery in acid secretion, for example, after treatment in thyrotoxicosis (Bock and Witts, 1963) and tropical sprue (Vaish, Sampathkumar, Jacob, and Baker, 1965) and also the apparently normal patient (Weir, 1967). Thus it is possible that many factors are involved in any one case.…”
mentioning
confidence: 99%